EFFECT OF ANTIMETABOLITE THERAPY ON N-GLYCAN EXPONATION ON THE MEMBRANES OF LYMPHOCYTES IN LEUKEMIA - Маслак, Г.С. (World of Medicine and Biology, 2014)
The N-glycans exponation on membranes of lymphocytes of patients with chronic lymphocytic leukemia, and polycythemia vera and subleukemic myelosis before treatment and after treatment were investigated and compared. Localization of N-glycotopes was determined by flow cytometry using concanavalin A – Con A conjugated with fluorescent labels. Number of Con A-positive lymphocytes in peripheral blood with chronic lymphocytic leukemia was 2.2 times higher as compared with the control group, while in polycythemia vera and subleukemic myelosis was in normal value. There is a significantly increasing in 20 times of Con A-positive epitopes in patients with chronic lymphocytic leukemia compared with the control group, and an absence of difference in patients with polycythemia vera and subleukemic myelosis. Carrying out fludarabine and cyclophosphamide therapy in patients with chronic lymphocytic leukemia, and treatment of patients hydroxycarbamide in polycythemia vera and subleukemic myelosis patients reduced the Con A-positive lymphocytes number and decreased N-glycotopes exponation intensity, which can indicate of universality the action of antimetabolites on leukemia.